Technical, economic and lifecycle greenhouse gas emissions analyses of solid sorbent direct air capture technologies - Sylvanus Lilonfe; Sarah Rodgers; Amir F.N. Abdul-Manan; Ioanna Dimitriou; Jon McKechnie (Carbon Capture Science & Technology)
Achieving net zero emissions by 2050 will require the development of cost-effective and CO2-efficient direct air capture (DAC) technology to remove atmospheric CO2. This study presents a comprehensive assessment of five solid sorbents under different technology scenarios to determine the design, operations, cost and greenhouse gas (GHG) emissions of DAC technologies. The cost and GHG emissions of the five solid sorbents ranged from $20241,200–40,400/t sorbent and 3.1–12.3 tCO2e/t sorbent in 2024, respectively, mainly driven by the raw materials used for sorbent manufacture. Cost estimates for the best capture technologies ranged from $202497–168/gross tCO2 captured [$2024126–170/net tCO2 captured] in 2025 and can be further reduced to $202487–140/gross tCO2 captured [$202493–142/net tCO2 captured] in 2050. The costs of DAC are heavily influenced by: (i) economic factors (i.e. capital expenses and energy costs), (ii) design elements (i.e. plant scale) and (iii) technical parameters (i.e. sorbent's adsorption rate and time). Conversely, the GHG emissions of DAC are mostly determined by the source of energy. Price signals in existing carbon markets are inadequate to support a DAC project, but a forecasted carbon price increase to $140–240/tCO2 by 2030–2050 could make DAC commercially viable.